Multi-receptor drug design: Haloperidol as a scaffold for the design and synthesis of atypical antipsychotic agents - Peprah, Kwakye (2011)
Using haloperidol as a scaffold, new agents were designed to investigate the structural contributions of various groups to binding at CNS receptors associated with atypical antipsychotic pharmacology. It is clear that each pharmacophoric group, the butyrophenone, the piperidine and the 4-chlorophenyl moieties contributes to changes in binding to the receptors of interest. This strategy has resulted in the identification of several new agents, compounds 16, 18, 19, 23, 24 and 25, with binding profiles which satisfy our stated criteria for agents to act as potential atypical antipsychotics. This research demonstrates that haloperidol can serve as a useful lead in the identification and design of new agents that target multiple receptors associated with antipsychotic pharmacology.